Integrative taxonomy of Hemimycale (Hymedesmiidae: Poecilosclerida: Demospongiae) from Southeastern Brazil, with the description of two new species - Huguenin, Larissa; Salani, Sula; Lopes, Maira F.; Albano, Rodolpho M.; Hajdu, Eduardo; Esteves, Eduardo Leal (Zootaxa, 2018)
Two new species of Hemimycale from Southeastern Brazil are described in this study with the use of morphological and molecular data. Hemimycale oxeata sp. nov. is orange salmon colored in life and has unique oxeote like tornote spicules in addition to the typical (subtylo-)strongyles of the genus. Hemimycale ceadensis sp. nov. is reddish orange in life and has raised, tiny pore sieves, and subtylostrongyles with asymmetrical ends and raphides as microscleres. The diagnosis of the genus Hemimycale was slightly modified for the inclusion of the new species. Maximum-Likelihood analyses of 18S rRNA and COI sequences resulted in the clustering of both new species with the type species of the genus, thus confirming our morphological identification. The value of anatomical characters of pore sieves for diagnosing species and the genus is discussed. A key for species identification is also furnished.